KUALITAS DAN SKILL IT PADA AUDITOR INTERNAL: SYSTEMATIC LITERATURE REVIEW - Erika Fara Rosadina; Totok Dewayanto (Diponegoro Journal of Accounting, 2023)
The objective of this research is to investigate the Quality and IT Skills in Internal Auditing. This study also aims to indentify the diversity of outcomes in terms of recommendations and contributions. This research utilized the Systematic Literature Review (SLR) method to analyze and identify various articles published in academic journals indexed in Scopus. Spanning from 2020 to 2022. The focus of the review was on articles discussing internal audit in retaion to quality and IT Skills. The SLR method was employed to identify researchers recomendations, and the limitation of the published studies. The analysis results indicate that academic studies emphasize the importance of Quality and IT Skills in supporting the Internal Audit Process. By enchancing the Quality and IT Skills, it is possible to improve performance and facilitate the completion of tasks. Additionally, it can lead to producting of higher-quality reports. Furthermore, the findings suggest that improving Quality and IT Skills has an impact on a company’s internal controls, making it easier for company to implements improvements and enchancements in its internal control systems. This, in turn, can attract investor interest and be beneficial for the company, it also helps in improving the finansial performance of the company. Moreover, the study reveals that enhancing Quality and IT Skills has a positive influence on auditors as its can affect their emotional intelligence, enabling them to perform their tasks more effectively and efficiently, consequently, research focusing on the Quality and IT Skills in Internal Auditing holds significant appeal for further studies. The findings of this study are expected to provide benefits to auditors, companies utilizing internal and external auditors, by recommending improvements in the quality and IT Skills required for the Internal Audit Process.